Overcoming Marital Dependency in Domenico Starnone’s “Ties” 2017 - Sakti, Andhika Dwi; Wahyuni, Delvi (Universitas Negeri Padang, 2023)
This study is an analysis of a novel entitled Ties (2017) by Domenico Starnone. This analysis explores the issue of wife's dependency on the husband. The aim of this study is to explain the circumstances that have led the character to become dependent on her husband by applying feminist literary theory. The results of this study show that there are three circumstances, namely traditional gender roles, economic dependency and emotional dependency.